Generation of inhibitory peptides for IKKε from a kinase‐focused phage library of helix‐loop‐helix peptides. Issue 3 (15th December 2021) - Mihara, Kousuke; Nakajima, Natsumi; Fujii, Ikuo; Fujiwara, Daisuke
Abstract: Conformationally constrained peptides are attracting attention as peptide‐based molecular tools in chemical biology and drug discovery because of their desirable properties such as high selectivity for target binding and stability toward proteolytic enzymes. We previously reported a protein kinase–focused helix‐loop‐helix (HLH) peptide library. The library was constructed by phage display and subsequent chemical modification with adenosine that was employed as an anchor molecule binding to the ATP‐binding pocket of kinase. Here, we discovered and characterized HLH peptides that bind to and inhibit the serine/threonine protein kinase IKKε, a member of the IκB kinase (IKK) family. Screening the library against IKKε identified de novo HLH peptides binding to the kinase. One of the peptides, IKK‐05, showed a high α‐helical content and inhibited IKKε with a mixed‐inhibition mechanism with respect to ATP. The adenosine‐tethering peptide Adc‐IKK‐05 demonstrated significantly enhanced enzyme inhibition activity, indicating a bivalency effect in binding to IKKε. In addition, Adc‐IKK‐05 showed the highest inhibitory activity against IKKε of the IKK family members and other families tested. The peptides obtained in this research can be developed as molecular tools to study the biological functions of IKKε and to obtain structural insights for the design of selective IKKε inhibitors. Abstract :